Project Based Learning Toward Students’ Creativity In Speaking Performance - Qomariyah, Siti Syafi’atul; Heri Hidayatullah; Tama Krisnahadi (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
This study aimed to find out whether or not Project based Learning have impact toward students’ creativity in speaking performance. This research was experimental research with quasi experimental design. This research was conducted on second semester of English language education as population which was consisted of 30 students (Experimental Class) and 30 students (Control Class). To determine the sample, the researchers used random sampling technique. Instrument of this research was verbal creativity test. It consisted of several sub-test such as guest, guessing causes and guessing consequences, unusual use activities, improvement activities, and just suppose activity. The data analyzed used SPSS to determine descriptive and inferential statitistics. Based on the data analysis showed that t-test was 7.140 in 5% level of significant. It proved that Project based Learning has significant impact in students’ creativity in speaking performance